2014
DOI: 10.1016/j.ndteint.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new in situ test method to measure the air permeability of high performance concretes

Abstract: Although several in situ techniques, including the Autoclam Permeability System, are available to examine normal concretes (NCs) for this purpose, none are sufficiently sensitive to quantify and distinguish relative high performance concrete (HPC) performance. Therefore, to assess the HPC performance characteristics using the Autoclam air permeability test methodology, two key modifications were investigated and a new test protocol developed. The first modification considered a reduced volume of compressed air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 26 publications
(51 reference statements)
2
32
0
2
Order By: Relevance
“…From previous research, a drying temperature of 40 o C has been reported as appropriate for minimising cementitious microstructural alteration and capable of determining free moisture contents of NC and AASC samples [11,27,30] and removing moisture effects on permeation results of a range of concrete types [11,29]. As such, the temperature of 40 o C was chosen as the pre-conditioning drying temperature for AASC in this study.…”
Section: / 26mentioning
confidence: 99%
See 4 more Smart Citations
“…From previous research, a drying temperature of 40 o C has been reported as appropriate for minimising cementitious microstructural alteration and capable of determining free moisture contents of NC and AASC samples [11,27,30] and removing moisture effects on permeation results of a range of concrete types [11,29]. As such, the temperature of 40 o C was chosen as the pre-conditioning drying temperature for AASC in this study.…”
Section: / 26mentioning
confidence: 99%
“…To assess gel porosity, the cores were then placed in an oven at 105 o C to reach the mass equilibrium state (M105C). These procedures were developed based on the previous studies [11,27,29,30]. …”
Section: Specimen Preparationmentioning
confidence: 99%
See 3 more Smart Citations